Soft Pneumatic Exoskeleton for Wrist and Thumb Rehabilitation - Sa’aadat Syafeeq Lone; Norsinnira Zainul Azlan; Norhaslinda Kamarudzaman (Association for Scientific Computing Electronics and Engineering (ASCEE), 2021)
A huge population of the world is suffering from various kinds of disabilities that make basic daily activities to be challenging. The use of robotics for limb rehabilitation can assist patients to recover faster and reduce therapist to patient ratio. However, the main problems with current rehabilitation robotics are the devices are bulky, complicated, and expensive. The utilization of pneumatic artificial muscles in a rehabilitation system can reduce the design complexity, thus, making the whole system light and compact. This paper presents the development of a new 2 degree of freedom (DOF) wrist motion and thumb motion exoskeleton. A light-weight 3D printed Acrylonitrile Butadiene Styrene (ABS) material is used to fabricate the exoskeleton. The system is controlled by an Arduino Uno microcontroller board that activates the relay to open and close the solenoid valve to actuate the wrist. It allows the air to flow into and out of the pneumatic artificial muscles (PAM) based on the feedback from the sliding potentiometer. The mathematical model of the exoskeleton has been formulated using the Lagrange formula. A Proportional Integral Derivative (PID) controller has been implemented to drive the wrist extension-flexion motion in achieving the desired set-points during the exercise. The results show that the exoskeleton has successfully realized the wrist and thumb movements as desired. The wrist joint tracked the desired position with a maximum steady-state error of 10% for 101.45ᵒ the set point.